Vitamin K-dependent synthesis and modification of precursor prothrombin in cultured H-35 hepatoma cells. - Munns, T W (1976)
The ability of confluent monolayers of H-35 cells, originally obtained from a rat hepatoma, to synthesize prothrombin in response to vitamin K1 (phylloquinone) was studied. As demonstrated by radioimmunoassay, selective barium salt adsorption, and two coagulation assays which discriminate between precursor- and mature-prothrombin, these cells retained their ability to synthesize precursor prothrombin (preprothrombin) in the absence of exogenous phylloquinone (vitamin K). When phylloquinone was added to the medium (100 ng/ml), the existing intracellular concentration of preprothrombin was reduced to 50% within 1 hr after exposure to the vitamin and slowly declined thereafter to approximately 30% of control levels by 36 hr. Concomitant with the rapid loss of intracellular preprothrombin was the appearance of mature prothrombin in the medium. The appearance of prothrombin was biphasic: occurring during the initial 0-6 hr interval, and again at an increased rate during the next 18-24 hr interval. The amount of prothrombin appearing in the medium exceeded by severalfold the amount of precursor mobilized. These data demonstrate that monolayer cultures of H-35 hepatoma cells retain their ability to synthesize preprothrombin and other enzymes, responsible for post-translational modification of prothrombin and its subsequent secretion, under the influence of vitamin K.